Scheduling Analysis on the Heavy Rehabilitation Construction Project of the Dr. R. Koesma Tuban Hospital Building Using the PERT Method - Putra, Edy Sutrisno; Rodhi, Nova Nevila; Ratnasari, Ayu Kurnia (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
Project scheduling is a key factor in achieving successful implementation as planned. Constraints such as limited resources, improper reporting, and high costs often become challenges in project management. Delays in project completion are very detrimental both in terms of cost and time. Just like what happened in the Rehabilitation and Heavy Construction Project of the Outpatient and Administration Building at Dr. R. Koesma Regional General Hospital in Tuban Regency, there was a delay of 10 days in its implementation. This research aims to determine the duration of the rehabilitation of the dr. R. Koesma Hospital building in Tuban Regency using the PERT method to improve time efficiency, reduce the risk of delays, and ensure overall project success. The research method used is combining two approaches, PERT method (Program Evaluation and Review Technique) to calculate the expected duration estimation of each work, and Microsoft Project 2016 to compile a project schedule that allows identification of critical activities and work network analysis. The results of the analysis using PERT method and Microsoft Project 2016 showed that the project was estimated to be completed in 115 days, faster than the planned 133 days. The probability that the project will be completed within the planned target duration T(d) = 133 days is 99.9%. Hence, there is a high probability that the project will be completedÂ onÂ time.